EFFECT OF PERFLUORANE ON THE REGULATION OF SKIN BLOOD FLOW IN ACUTE BLOOD LOSS: EXPERIMENTAL STUDY - I. A. Ryzhkov; Yu. V. Zarzhetsky; I. S. Novoderzhkina (Общая реаниматология)
Objective: to use laser Doppler flowmetry (LDF) to investigate the effect of perfluorane on the time course of microhemocirculatory changes in the rat skin in acute blood loss and after autohemotransfusion.Materials and methods. Experiments were carried out on 31 outbred male rats weighing 300—400 g under anesthesia with intraperitoneal Nembutal 45 mg/kg. The caudal artery was catheterized to measure blood pressure (BP), to sample and reinfuse blood, and to administer infusion solutions. The LDF (ЛАКК-02 device, LAZMA, Russia) method was used to record blood flow in the microvessels of the internal surface of the right ear. A volume-fixed acute blood loss model was applied. The goal amount of blood loss was 30% of the circulating blood volume. At 10 minutes after blood sampling, the animals were administered with 0.9% NaCl solution (physiologic saline (PS), n=15) or perfluorane, PF, n=16 at in a dose of 3 ml/kg body weight. At 60 minutes following blood sampling, autohemotransfusion was carried out, after which there was a 60 min reperfusion period. The investigators ana lyzed LDF readings and determined the following indicators: microcirculation index (MI); the maximum ampli tudes of blood flow fluctuations in the endothelial (Ae), neurogenic (An), and myogenic (AM) frequency ranges by a wavelet analysis. The data were statistically processed using Statistica 7.0 software. Results. At baseline, no differences were found between the PF and PS groups in the examined indicators. At 1—10 min of hypovolemia (before drug administration), as compared with the baseline values, both groups showed equal changes as reductions in blood pressure (BP) (by 58.3 and 62.2% in the PS and PF groups) and MI (by 63.3 and 69.2% in the PS and PF groups) and an increase in An (P<0.05). After drug injections, BP and MI were increased in both groups, but to a greater extent in the PF group (P<0.05); Ae also rose in both groups, and An continued to remain higher. During hypovolemia, BP values were thereafter similar in both groups and An remained elevated as compared to its baseline values, at the same time Ae remained increased in the PF group only. During reperfusion, MI, Ae, and An returned to their baseline values in both groups. BP returned to its baseline values and was kept constant in the PS group and decreased in the PF group at 50—60 min versus 1—10 min of reperfusion and outcome. The differences in BP had no impact on the microcirculatory parameters examined.Conclusion. The administration of PF versus PS in acute blood loss causes a more pronounced increase in BP and MI. The Ae increase persisting in the PF group throughout hypovolemia may point to the stimulating effect of PF on the endothelium-dependent mechanisms of flux motions in the rat ear skin under hypovolemic conditions.